Loosening the grip : - Kinney, Jean (McGraw-Hill, 2012)
Loosening the Grip is widely recognized as a useful resource for future and current health care workers: substance abuse clinicians, school counselors, mental health workers, community nurses, and others. As noted on the website for the Substance Abuse and Mental Health Services Administration (SAMHSA): “There are many helpful books on alcohol and alcoholism. Loosening the Grip: A Handbook of Alcohol Information by Jean Kinney is a good place to start.”